KONFLIK PERAN GANDA PARA PENGUSAHA PEREMPUAN PADA USAHA KECIL DI MADURA - Anshori, Muhammad Isa (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
This research is aimed to investigate the influence of business-related factors, family-related factors, and personal factors on the dual role existence. Batik industry is used as the research target since over 50% of the entrepreneurs are women. The research used 54 respondents as a sample located in Tanjung Bumi which cover 3 areas: Tanjung village, Telaga Biru village and Paseseh village. The result of this research shows that comfortable life, self-respect, business satisfaction, time of work, children and the liquidity of the business have significant influence on dual role to the women entrepreneurs in Batik industry in Bangkalan Madura.